Estimating School Effects with a State Testing Program Using Transition Matrices. Issue 3 (3rd July 2017) - Tindal, Gerald; Nese, Joseph F. T.; Stevens, Joseph J.
ABSTRACT: For the past decade, the accountability model associated with No Child Left Behind (NCLB) emphasized proficiency on end of year tests; with Every Student Succeeds Act (ESSA) the emphasis on proficiency within statewide testing programs, though now integrated with other measures of student learning, nevertheless remains a primary metric for reporting achievement. We examine transition over categories across two years for three cohorts of middle school students as one means for evaluating change. We document school effects for seven models by analyzing relations among them and comparing them to the actual change in movement across categories. We report moderate to high correlations across the transition models though they differed vastly in the (a) assumptions behind them, and (b) ranking of schools with actual transitions. The findings, therefore, need to be considered in the context of assumptions embodied in each transition model to adequately understand their worth in reporting school effects.